Pengaruh Variasi Waktu Inkubasi terhadap Kadar Hemoglobin Menggunakan Metode Sahli: The Effect of Incubation Time on Hemoglobin Levels using Sahli Method - Ardina, Rinny; Putri, Yemimasike (Borneo Journal of Medical Laboratory Technology, 2019)
Several clinical laboratory and community health centers in Palangka Raya still use a simple method to determine hemoglobin levels with Sahli method. There are mamy differences in procedures related to incubation time in Sahli method of hemoglobin examination. There are those who don’t use incubation, incubation for 3 minutes or incubation for 5 minutes. This study aimed to determine the effect of icubation time on hemoglobin levels using the Sahli method. This study was experimental study, where hemoglobin levels are measured by Sahli method with incubation time variations of 0 minutes, 3 minutes, 5 minutes, 8 minutes, and 10 minutes. A total of 21 blood samples were obtained by purposive sampling technique. The data obtained were statistically analyzed using the One Way ANNOVA test. The results showed there are significant effect of incubation time (0 minutes, 3 minutes, 5 minutes, 8 minutes and 10 minutes) on hemoglobin levels using Sahli method (p = 0.00). Increased hemoglobin levels occur with increasing incubation time. Where the lowest value of the average hemoglobin level at the measurement of 0 minutes was 10.9 g / dl and the highest value on the measurement of 10 minutes was 14.2 g / dl. It is important to laboratory personnel to incubate blood according to the procedures established by the Sahli method, because errors in the analytical stage contribute 25% to the causes of errors in laboratory result.